A multicenter evaluation of a new therapeutic plasma exchange procedure. Issue 12 (15th April 2013) - Winters, Jeffrey L.; Burgstaler, Edwin A.; Gottschall, Jerome L.; Balogun, Rasheed A.; Houghton, Jaime R.; Lee, Wanda J.; Snyder, Edward L.
<x xml:space="preserve">Abstract</x> Background The AMICUS (Fenwal, Inc.) was cleared in the United States for platelet (PLT) and plasma collection in 1996 with subsequent clearances for the collection of other blood products. Although not previously used for therapeutic plasma exchange (TPE), new disposables, software, and hardware were developed to enable TPE on the AMICUS. Study Design and Methods A multicenter, randomized, nonblinded, crossover paired treatment protocol was performed. Thirty patients with orders for at least two TPE procedures were randomly assigned to the AMICUS or the COBE Spectra (TerumoBCT) for the first treatment. Each patient was crossed over to the other device using the same procedure settings from the first procedure. The primary objective compared efficiency of plasma removal (EPR) with secondary objectives of comparing PLT and hemoglobin (Hb) waste plasma content, coagulation factor and complement activation, fluid balance tracking accuracy, procedure length, and adverse events. Results The EPR for the AMICUS (81.9 ± 7.62%) was superior to that of the COBE Spectra (75.2 ± 6.29%; p = 0.00001). The AMICUS also demonstrated statistically higher fluid balance accuracy (99.84%) compared to that of the COBE Spectra (98.83%; p < 0.0001) and a statistically shorter procedure time (103.9 ± 30.8 vs. 110.5 ± 27.1 min, p < 0.001). No significant differences with regard to PLT and Hb content in the waste plasma, change in patient PLT count, or changes in markers of coagulation and complement cascade activation were seen. Frequency and severity of adverse reactions were similar. Conclusion The AMICUS separator can effectively perform TPE. The AMICUS demonstrated superior plasma removal efficiency compared to the COBE Spectra with no evidence of significant differences in PLT removal, hemolysis, and coagulation or complement activation.